2000
DOI: 10.1055/s-2007-978617
|View full text |Cite
|
Sign up to set email alerts
|

Excess of Glucocorticoids Impairs Whole-Body Antioxidant Status in Young Rats. Relation to the Effect of Dexamethasone in Soleus Muscle and Spleen

Abstract: The action of glucocorticoids in high doses is catabolic, but not much is known about the accompanying effects on antioxidative capacity of the entire body. Animals were treated (or not) with dexamethasone (Dex) 2 mg/kg b.w. d-1 during 5 consecutive days followed by recovery, during which an additional group received 3-hydroxy-3-methylbutyrate (40 mg/kg b.w.). Animals were killed after treatment with Dex, and after 5 days of the recovery period. Dexamethasone treatment decreased appetite almost twofold (from 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
32
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(34 citation statements)
references
References 12 publications
2
32
0
Order By: Relevance
“…In a series of in vitro experiments these authors have shown that dexamethasone represses the activity of genes encoding antioxidant enzymes leading to impaired viability and apoptotic cell death [5,9]. Our own in vivo study performed on rats corroborates the working hypothesis that high doses of glucocorticoids are involved in the suppression of antioxidant defense systems and lead to growth retardation and muscle cachexia [34]. Muscle cells proliferate in growth-promoting conditions while becoming post-mitotic and fusing into multinucleated myotubes when deprived of serum mitogens.…”
Section: Cell Culturesupporting
confidence: 77%
“…In a series of in vitro experiments these authors have shown that dexamethasone represses the activity of genes encoding antioxidant enzymes leading to impaired viability and apoptotic cell death [5,9]. Our own in vivo study performed on rats corroborates the working hypothesis that high doses of glucocorticoids are involved in the suppression of antioxidant defense systems and lead to growth retardation and muscle cachexia [34]. Muscle cells proliferate in growth-promoting conditions while becoming post-mitotic and fusing into multinucleated myotubes when deprived of serum mitogens.…”
Section: Cell Culturesupporting
confidence: 77%
“…Intrauterine oxidative stress could be attributed to exposure to excess maternal glucocorticoids (21,30) and to nutrient restriction, which can, in itself, induce oxidative stress in the pregnant dam with placental and potentially fetal repercussions (13). In addition, elevated glucocorticoids can increase the susceptibility to oxidative stress, especially in young animals, in part through impairment of antioxidant status (1,11,56,57). Therefore, the combination of increased production of ROS by ANG II and decreased antioxidant capacity (through nutrient restriction and exposure to excess glucocorticoids) can increase the susceptibility of the "programmed" fetus to oxidative stress at birth when tissue PO 2 increases dramatically.…”
Section: Discussionmentioning
confidence: 99%
“…In this condition, the excessive production of superoxide anions, which participate in vascular dysfunction and remodeling seems secondary to the increased activation of the NADPH oxidase by ANG II (46). Considering the early role of the RAS in programmed HT (68), the impaired antioxidant defenses associated with fetal malnutrition (28,45) and the fact that glucocorticoids have been shown to enhance susceptibility to oxidant stress (1,56), especially in younger subjects (11,57), one can postulate that infants born after intrauterine deprivation or who are relatively immature are at risk of sustaining early oxidative stress, which could lead to altered cardiovascular development and long-term consequences.…”
mentioning
confidence: 99%
“…High levels of glucocorticoids have been reported to decrease blood glutathione and erythrocyte superoxide dismutase activity in rats (ORZECHOWSKI et al, 2000) and goats (ALILA JOHANSSON et al, 2003). BHAT et al (2008) reported that the high temperature and humidity of summer increase neuroendocrine stress and lipid peroxidation, which contribute to reduced erythrocyte antioxidant response in rats.…”
Section: Discussionmentioning
confidence: 99%